Mineralogy dictates the initial mechanism of microbial necromass association. (1st September 2019) - Creamer, Courtney A.; Foster, Andrea L.; Lawrence, Corey; McFarland, Jack; Schulz, Marjorie; Waldrop, Mark P.
Abstract: Soil organic matter (SOM) improves soil fertility and mitigates disturbance related to climate and land use change. Microbial necromass (the accumulated cellular residues of microorganisms) comprises the majority of soil C, yet the formation and persistence of necromass in relation to mineralogy is poorly understood. We tested whether soil minerals had different microbial necromass association mechanisms. Specifically, we tested whether microbial necromass directly sorbed to mineral surfaces or was consumed by live microorganisms prior to mineral association. Applying Raman microspectroscopy with 13 C enriched microbial necromass to quantify microbe-mineral interactions, we show that mineralogy alters the initial mechanism of microbial necromass association. In the presence of K-feldspar (lower abiotic C preservation potential), microbial necromass required assimilation by live microorganisms for mineral retention. In contrast, with amorphous aluminum hydroxide (higher abiotic C preservation potential) microbial necromass was retained predominately through abiotic sorption, and was subsequently protected from microbial decomposition. Despite different mechanisms, both minerals retained similar quantities of microbial necromass under biotic conditions. Mineralogy determined not only the quantity of mineral-associated C, but the distinct pathway of microbial necromass association. These findings show the utility of Raman microspectroscopy as a technique to study microbe-mineral interactions, and imply that heterogeneity in mineral-organic interactions could result in gradients of organic matter stability.